Pendidikan Kesehatan Gigi dan Mulut serta Praktek Menggosok Gigi Pada Anak Berkebutuhan Khusus (ABK) - Betty Saptiwi; Risya Cilmiaty; Widia Susanti; Selfi Handayani (Abdimas Universal, 2019)
Special Needs Children in SLB Anugerah, Colomadu, Karanganyar, Central Java, are still difficult to practice how to brush teeth correctly and still lack of understanding of oral health, so that the hygiene and dental health status and mouth are still lacking. Therefore it is necessary to fix it. The purpose of this activity is to carry out one component of the Higher Education Tri Dharma that is community service. The benefits of this service are for special needs students to increase their knowledge about oral health and improve their skills in brushing their teeth properly. The dedication method is a lecture on how to maintain dental and oral health as well as the practice of brushing teeth along with the target audience, all Special Needs Children in SLB Anugerah, Colomadu, Karanganyar. A total of 52 people were present. The results of the dedication showed that 42.3% of the targets were able to practice brushing teeth with enough categories and 57.7% were still in the poor category. Meanwhile, no one has been categorized as good. The conclusion of this dedication is, the practice of brushing Special Needs Children teeth in SLB Colomadu, Karanganyar is still in the category of sufficient and insufficient so that it is necessary to follow up this service activity by involving parents at home in monitoring the maintenance of dental and oral health of Special Needs Children.